Past and Present Legal Medicine in Peru - Avendaño H., Jorge (1960)
It is very difficult to pinpoint the beginning of our specialty in a country like most South Americans, has evolved through the ages Inca, Colonial and Republican. Credible reports of the first one have been studied in Peru by various medical researchers, especially Hermilio Valdizán and John B. Ballasts, both noticeably missing, and his writings have not found anything concerning the Medical-Legal science, which is not surprising since the existence of Legislation Inca and possible intervention is ignored his doctors-if any-or at least their healers, great observers as evidenced by the remarkable pieces of anthropomorphic pottery, may have had legal issues .